2012
DOI: 10.3138/cjwl.24.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Why Feminist Legal Scholars Should Write Judgments: Reflections on the Feminist Judgments Project in England and Wales

Abstract: Le Projet de jugements féministes a permis à des chercheuses en droit féministes de rédiger en groupe des jugements féministes alternatifs pour des causes majeures en Angleterre et au Pays de Galles. Plutôt que de se limiter à des critiques théoriques de décisions existantes, les participantes se sont inscrites dans la tradition du Tribunal des femmes du Canada pour se lancer dans un exercice pratique et « réaliste » de rédaction de jugements. En exprimant la théorie féministe sous forme de jugements, le Proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For example, a Wild Law Project is currently underway which seeks to redraft judgments from an environmental or earth-centred perspective: http:// www.earthlaws.org.au/events/wild-law-judgment-project/. See Rackley (2012) for an account of judgment writing as critique where she also notes its use in Constitutional and strictly jurisprudential exercises. Interestingly, she notes Fuller's use of narrative technique in drafting the entirely fictional judgment, 'Case of the Speluncean Explorers'.…”
Section: The Feminist Judgmentmentioning
confidence: 97%
“…For example, a Wild Law Project is currently underway which seeks to redraft judgments from an environmental or earth-centred perspective: http:// www.earthlaws.org.au/events/wild-law-judgment-project/. See Rackley (2012) for an account of judgment writing as critique where she also notes its use in Constitutional and strictly jurisprudential exercises. Interestingly, she notes Fuller's use of narrative technique in drafting the entirely fictional judgment, 'Case of the Speluncean Explorers'.…”
Section: The Feminist Judgmentmentioning
confidence: 97%
“…The recent feminist judgment projects (Douglas et al, 2014a;Enright et al, 2017;Stanchi et al, 2016;Women's Court of Canada, 2006), and theorizing around them (e.g. Davies, 2012;Fitz-Gibbon and Maher, 2015;Hunter, 2008Hunter, , 2010Hunter, , 2012Hunter, , 2013Hunter, , 2015aHunter, , 2015bHunter et al, 2016;Rackley, 2012), have identified a variety of practices which might be identified as 'feminist' judging. One key insight from these projects is that a feminist approach is at least as, if not more, likely to be found in judicial reasoning than in the outcome of a case.…”
Section: Positive Endorsement Of Legislative Reformmentioning
confidence: 99%
“…In this context, this type of violence is not simply the outcome of a sudden raptus or a moment of madness but the result of the will to subjugate women. Interestingly, the belief that feminist judges will make the difference is supported by feminist judgment projects: collaborations between feminist legal scholars who rewrote selected legal decisions to show that the cases could have been decided differently if magistrates were loyal to concrete women's lived experiences and not conditioned by gender stereotypes (Rackley, 2012).…”
Section: Introductionmentioning
confidence: 99%